2009
DOI: 10.1158/1078-0432.ccr-08-0889
|View full text |Cite
|
Sign up to set email alerts
|

Marked Activity of Irinotecan and Rapamycin Combination toward Colon Cancer Cells In vivo and In vitro Is Mediated through Cooperative Modulation of the Mammalian Target of Rapamycin/Hypoxia-Inducible Factor-1α Axis

Abstract: Purpose: Despite recent progress, colon cancer is often resistant to combination chemotherapy, highlighting the need for development of novel therapeutic approaches. An attractive target is hypoxia-inducible factor-1a (HIF-1a), a key transcription factor with a pivotal role in tumor cell metabolism. One potential class of therapeutic agents targeting HIF-1a are mammalian target of rapamycin inhibitors such as rapamycin. A second class are topoisomerase I inhibitors, such as irinotecan, which are able to inhibi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 43 publications
4
50
0
Order By: Relevance
“…Reduced expression of these genes may result in decreased ATP production by the glycolytic pathway, which is needed for tumor growth during hypoxia (32,33). This in vivo signature is in agreement with our previous observations showing that downregulation of HIF1A by siRNA in colon cancer cells induces antiproliferative effects in hypoxia conditions, validating HIF1A as a functionally important target (21).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Reduced expression of these genes may result in decreased ATP production by the glycolytic pathway, which is needed for tumor growth during hypoxia (32,33). This in vivo signature is in agreement with our previous observations showing that downregulation of HIF1A by siRNA in colon cancer cells induces antiproliferative effects in hypoxia conditions, validating HIF1A as a functionally important target (21).…”
Section: Discussionsupporting
confidence: 91%
“…These results are also consistent with those reported for topotecan, another topoisomerase I inhibitor that did not affect HIF1A mRNA accumulation or protein half-life, but rather acted on the translational level (54). In addition, we have recently shown that inhibition of HIF1A protein accumulation by irinotecan does not rely on inhibition of the mammalian target of rapamycin (mTOR) pathway (21).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…E and F, effects of CPT-11 and/or tirapazamine on expression levels of HIF-1a in Bel-7402 cellderived tumors were determined by H&E staining and immunohistochemical and immunofluorescence analysis. a protective effect against DNA damage induced by topoisomerase inhibitors (32,33). As shown in Supplementary Fig.…”
Section: Discussionmentioning
confidence: 76%
“…Rapamycin is a mTOR inhibitor that shows potent antitumor activity in a variety of malignances including ovarian cancers in preclinical and clinical studies [8][9][10]. Notably, rapamycin and its derivatives have been demonstrated to enhance the efficacy of cytotoxic chemotherapeutic drugs including topotecan, oxaliplatin, and 5-fluorouracil (5-FU) against various types of cancers such as endometrial, gastric and colon cancer [8,[11][12][13][14]. Given that mTOR signaling pathway was shown to be hyperactivated in platinum-resistant ovarian carcinoma cells [15], we investigated the efficacy of combination of topotecan with rapamycin against cisplatin-resistant ovarian carcinoma in the present study.…”
mentioning
confidence: 99%